THE EFFECT OF DIVIDEND POLICY, LEVERAGE, AND PROFITABILITY ON FIRM VALUE WITH SALES GROWTH AS A MODERATING VARIABLE - I Gusti Agung Ayu Manik Maharani; Anak Agung Gde Putu Widanaputra (Adisam Publisher, 2025)
Firm value represents the perception of investors toward a company and serves as one of the indicators for potential investors when making investment decisions. This study aims to analyze the effect of dividend policy, leverage, and profitability on firm value, with sales growth as a moderating variable. The research was conducted on companies in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. The sampling method used was purposive sampling, and a total of 141 samples were obtained. The analytical technique used was Moderated Regression Analysis (MRA). The results show that sales growth does not moderate the effect of dividend policy on firm value. Sales growth does not moderate the effect of leverage on firm value. Sales growth also does not moderate the effect of profitability on firm value.